Crosslinked polymer embedded Cu/Ag for comparative drug adsorption and kinetics evaluation - Mane, Sachin; Ponrathnam, Surendra; Chavan, Nayaku (International Journal of Polymeric Materials and Polymeric Biomaterials, 2016)
Two-dimensional crosslinked polymer (2-DCP) was synthesized for evaluation of drug adsorption and kinetics thereof. Further, polymer properties were evaluated and parameters such as contact time and adsorption isotherm were also studied. Herein, contact time demonstrated 83% and 85% of drug loading in an acidic medium for two-dimensional crosslinked polymer embedded copper and silver (2-DCP-Cu/Ag), respectively in 24h. Initial 4h is the exponential drug loading period whereas drug loading was increased gradually after 4h. Salbutamol loading was well-fitted to Langmuir adsorption isotherm, which indicated a monolayer drug adsorption with respect to 2-DCP-Cu/Ag. Pseudo first- and pseudo second-order kinetics was evaluated to perceive the drug adsorption mechanism and equilibrium adsorption capacity. Monolayer drug adsorption with chemisorption mechanism was observed for 2-DCP-Cu/Ag. In addition to this, decomposition temperature of polymer was 440 and 325 degrees C while glass transition temperature of polymer was 280 and 200 degrees C before and after metal modification, respectively. (A=aqueous phase; B=organic phase; C=drug solution; D=drug loaded polymer; E=enlarged drug loaded polymer.) [GRAPHICS] .
Keywords: Adsorption isotherm; adsorption kinetics; crosslink polymer; drug loading; langmuir adsorption isotherm; salbutamol

Interfacial tension approach toward drug loading with two-dimensional crosslinked polymer embedded gold: adsorption kinetics evaluation - Mane, Sachin; Ponrathnam, Surendra; Chavan, Nayaku (International Journal Of Polymeric Materials And Polymeric Biomaterials, 2016)
Interfacial tension of drugs with hydrophilic polymer (A) embedded gold resulting into selective drug adsorption, which also affected the drug adsorption kinetics. Two-dimensional crosslinked polymer embedded gold was synthesized for drug loading application in an acidic buffer. Lower interfacial tension of pantoprazole sodium (B) revealed the exponential loading inversely loading was gradual for chloroquine (C) having more interfacial tension with adsorbent. Initial 2 h was the exponential adsorption period for a pantoprazole sodium whereas exponential adsorption begins after 12 h for a chloroquine. Monolayer drug adsorption was obtained because Langmuir adsorption isotherm was obeyed by both drugs. Moreover, pseudo first-and pseudo second-order kinetics was also evaluated which demonstrated that reactive sites of the adsorbent are homogeneous and drug adsorption mechanism is chemisorption and not the physisorption. Thermal analysis was evaluated to confirm the polymer thermostability and glass transition temperature during catalytic applications in thermal reactions.
Keywords: Adsorption isotherm; adsorption kinetics; drug loading; drug polarity; Interfacial tension